Inheritance of resistance to the bean-pod weevil (Apion godmani Wagner) in common beans from Mexico - Garza García, Ramón; Cardona Mejía, César; Singh, Shree P. (1996)
The bean-pod weevil (BPW), Apion godmani Wagner, often causes heavy losses in crops of common bean (Phaseolus vulgaris L.). Farmers need resistant bean cultivars to minimize losses, cut production costs, stabilize seed yield, and reduce pesticide use and consequent health hazards. To design effective breeding methods, breeders need new and better sources of resistance and increased knowledge of their modes of inheritance. We therefore: (1) compared sources of resistance to BPW, (2) studied the inheritance of resistance, and (3) determined whether the sources possess similar or different genes for BPW resistance. The following sources of resistance, originating from the Mexican highlands, were evaluated for 3 years at INIFAP-Santa Lucía de Prias, Texcoco, Mexico: ‘Amarillo 153’, ‘Amarillo 169’, ‘Hidalgo 58’, ‘J 117’, ‘Pinto Texcoco’, ‘Pinto 168’, and ‘Puebla 36’. All except ‘Puebla 36’ were crossed with the susceptible cultivar ‘Jamapa’. ‘Amarillo 153’ and ‘Puebla 36’ were crossed with another susceptible cultivar, ‘Bayo Mex’. The parents, F1 hybrids, and F2 populations were evaluated for BPW damage in 1992. Backcrosses of the F1 of Jamapa/Pinto 168 to the respective susceptible and resistant parents were also evaluated in 1992. All seven resistant accessions were crossed in all possible combinations, excluding reciprocals. The resulting 21 F1 hybrids and 21 F2 populations were evaluated for BPW damage in 1994. ‘J 117’ had the highest level of resistance to BPW. ‘Pinto Texcoco’ and ‘Puebla 36’ had the highest mean damage score of all seven sources of resistance. The F1 hybrids between susceptible parents and resistant sources were generally intermediate. Two genes segregating independently controlled the BPW resistance in each accession. One gene, Agm, has no effect when present alone, whereas the other gene, Agr, alone conferred intermediate resistance. When both genes were present, resistance to BPW was higher. Based on mean BPW damage scores, all 21 F1 hybrids and their F2 populations, derived from crosses among seven resistant accessions, were resistant. However, data from individual plant damage scores in F2 populations of Amarillo 169/Pinto 168 and Pinto Texcoco/Pinto 168 suggested that at least one gene in each of the three accessions was non-allelic. Data also indicated that ‘Amarillo 169’ had a dominant gene that conferred high levels of BPW resistance, irrespective of the alleles at the other locus; and that ‘Pinto Texcoco’ and ‘Pinto 168’ possessed two different genes for intermediate resistance.